The abusive use of benzodiazepines in adult patients (Research, Society and Development, 2022)
Benzodiazepines developed a lot of popularity in the 1970s and 1980s due to their potential effectiveness for symptoms of anxiety, insomnia, aggressiveness, and seizures, among others. Currently, it is estimated that they are among the most prescribed drugs in Western countries, from this, one can observe the enormous presence of the use of this substance in everyday life. The literature describes those numerous factors are associated with the growing consumption of this class of drugs, such as stress, the consequent fragility of humanity to tolerate too much pressure, the introduction of new drugs, and even inappropriate prescribing habits by physicians. This research aimed to identify the effects of the abusive use of benzodiazepines by adults. This is an integrative review of literature from the last 10 years; the search occurred in the Scielo, BVS, Periodicals Capes and Pubmed databases. A total of 1401 studies were found, but after the screening and reading process only 10 were included in the review. The main findings point to the profile of the population and the reasons for the indiscriminate use of benzodiazepines. The study concludes that several factors corroborate for the indiscriminate use of anxiolytic drugs, their effect on the body for extended periods may even be irreversible, among the main problems identified the self-medication and easy access to benzodiazepines are the main ones reported in the literature.